ECONOMETRICAL METHODS OF MODELING AND FORECASTING THE ECONOMY OF THE REGION (FOR EXAMPLE, THE ROSTOV REGION OF RUSSIA) (Journal of Information Technologies in Education (ITE), 2012)
This article attempts to construct a model predicting the region's economy using econometric methods. Research is being conducted by the example of the Rostov region of Russia.
Keywords: econometrics; forecasting; modeling; Regional economy; trackanalysis